2019
DOI: 10.1016/j.molcel.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Ribonucleoprotein Granules Inhibit Translation in Protocells

Abstract: Highlights d New engineered phase-separating IDPs capable of binding RNA d IDPs co-phase-separate with RNAs into liquid granules in response to heat d IDP-RNA-rich granules regulate translation through mRNA sequestration d Droplet-based protocells temporally inhibit translation in a programmable manner

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 52 publications
(62 reference statements)
0
61
0
Order By: Relevance
“…Additionally, they constitute a powerful tool for studying the structural properties that are responsible for phase transition of complex IDPs and the subsequent formation of protein-rich biomolecular condensates. [5][6][7][8] One of the most important families of IDPPs that has received increased attention in biomedical studies and applications are elastin-like recombinamers (ELRs). 4 These protein-engineered polymers are structurally based on the conserved motifs of tropoelastin, generally based on the pentapeptide with a sequence X1-Pro-Gly-X2-Gly (where X1 can be Val or Ile and X2 can be any amino acid except L-Pro).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they constitute a powerful tool for studying the structural properties that are responsible for phase transition of complex IDPs and the subsequent formation of protein-rich biomolecular condensates. [5][6][7][8] One of the most important families of IDPPs that has received increased attention in biomedical studies and applications are elastin-like recombinamers (ELRs). 4 These protein-engineered polymers are structurally based on the conserved motifs of tropoelastin, generally based on the pentapeptide with a sequence X1-Pro-Gly-X2-Gly (where X1 can be Val or Ile and X2 can be any amino acid except L-Pro).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, decoding the sequence determinants of intrinsically disordered protein (IDP) phase separation is important for understanding the biochemistry of biomolecular condensates in physiological and pathophysiological conditions. Characterizing the effects of sequence on phase behavior is also important for the field of protein-based materials (17), wherein proteins can be designed to have desired characteristics and programable assembly (18)(19)(20), with applications in biotechnology such as drug delivery, cell engineering, and biomimetics (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…This mutation allowed the RGG domain to specifically recognize the RNA and was used to probe how TERRA regulates histone modifications (Takahama et al, ). Another more recent study used RGG domains fused to elastin‐like polypeptides to develop RBPs with tuneable phase behavior in protocells in an effort to study RBPs and RNA granules and showed that they granules can inhibit translation through either reversible or irreversible sequestration of mRNA (Simon, Eghtesadi, Dzuricky, You, & Chilkoti, ). Taken together these studies demonstrated that RGG boxes can be engineered for a variety of functions.…”
Section: Traditional Rbdsmentioning
confidence: 99%